Efektifitas Pendidikan Kesehatan Dengan Media Video Animasi Dan Flipchart Terhadap Pengetahuan Dan Sikap Ibu Dalam Penanganan Kejang Demam Di Rumah - Farah Luqyana (Jurnal Keperawatan Florence Nightingale, 2024)
The most common emergency condition in children is febrile seizures. The most common cause of errors in treating children with febrile seizures is parents' lack of knowledge about treating febrile seizures at home. Efforts that can be made to improve the knowledge and attitudes of parents, especially mothers, are by providing Health Education. This study aims to analyze the effectiveness of health education using animated video media and flip charts on mothers' knowledge and attitudes in handling febrile seizures. The research design used was Quasi-experimental with Pretest Posttest Non-equivalent Control Group Design and data collection using knowledge and attitude questionnaires in the pre-test and post-test. The sample used was 60 mothers of toddlers who were divided into two groups. Based on the results of research using the Wilcoxon test, it was found that Health Education using animated videos was effective on the knowledge of mothers of toddlers with a p-value of 0.000 and an N-gain value of 66.8% and was effective on mothers' attitudes in handling febrile seizures with a p-value of 0.000 and an N-gain value of 68.3%. So, it can be concluded that providing health education using animated videos is more effective in increasing mothers' knowledge and attitudes in handling febrile seizures. Thus, providing education using animated video media should be carried out more often on other health education topics to increase knowledge and positive attitudes in dealing with health problems.